FACTORS ASSOCIATED POST-PARTUM CONTRACEPTION PLANNING - Zulfa, Sheila Nurhaliza; Ayudha, Mita Dwi; Ernawaty, Ernawaty; Kurniawan, Afif (Jurnal Biometrika dan Kependudukan, 2024)
The problem of stunting that occurs in Indonesia is caused by one of the sensitive factors, namely bad parenting. Improper parenting can occur in mothers whose children are born too close together (<2 years). Postpartum contraception can also be a solution for those who are "4 too” The achievement of postpartum family planning services in Sarirejo District (65.12%) has not met the target (70%). This study aims to analyze the effect of age, number of children, level of education and knowledge of postpartum family planning plans for pregnant women in Sarirejo District. This type of analytic observational research with cross sectional design. The research subjects were all pregnant women in Sarirejo District in April 2023 with a total sample of 77 respondents. The results showed that the variables Age (p=0.001), Number of Children (p=0.001) and Knowledge (p=0.001) were related to postpartum contraceptive plans. Meanwhile, education level only at senior high school level (p=0.001) has an influence on postnatal contraceptive use plans. The conclusion is that postpartum contraceptive use increases with increasing maternal age, increases with increasing number of children, increases with maternal education and increasing knowledge. There is a need to increase understanding and knowledge of pregnant women about the importance of postnatal family planning through counseling and collaboration with village midwives.